Research progress on hyperbaric oxygen therapy for refractory peptic ulcer disease - Chen, Ze-Ming; Li, Wei-Feng; Yu, Xi-Qiu; Tang, Xiao; Yang, Qin-Hua; Wei, Xiao-Lan (Frontiers in Medicine, 2025)
Refractory peptic ulcer disease (RPUD) refers to gastric and duodenal ulcers that remain unhealed after 8–12 weeks drug treatment or are associated with complications despite drug treatment. Peptic ulcer disease is non-responsive to many treatments, has high recurrence rates, and often results in long-term pain, thus posing a persistent clinical challenge. Although the application of proton pump inhibitors has improved the healing rate and prognosis of patients with RPUD, drug efficacy is often limited by the emergence of drug resistant Helicobacter pylori and may be further reduced after co-application of non-steroidal anti-inflammatory drugs. Recent studies have demonstrated promising therapeutic outcomes of hyperbaric oxygen therapy (HBOT) in the management of refractory inflammatory bowel disease (IBD). Notably, emerging evidence further highlights the significant efficacy of HBOT in treating refractory peptic ulcers. In light of these findings, this review provides a systematic overview of the current research progress on HBOT for the treatment of RPUD.